KESTABILAN GLOBAL TITIK EKUILIBRIUM PADA MODEL VAKSINASI HUMAN PAPILLOMAVIRUS (HPV) YANG MELIBATKAN DUA POPULASI DENGAN JENIS KELAMIN BERBEDA - , IRMA SURYANI; , Dr. Fajar Adi Kusumo, S.Si., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
HPV is a major cause of cervical cancer, precancerous lesions, cancer and other illness. HPV can affect men and women so that the required vaccines for prevention. HPV vaccines now used to prevent cervical cancer and genital warts cause because the vaccine protects against four types of HPV that most commonly cause disease are types 6,11,16 and 18. This paper reviews the work and connect from Elbasha (2008). Global stability of the equilibrium point on the model of a two-sex HPV vaccination was investigated by using Lyapunov. The results show that the global stability of the equilibrium point depends on the effective reproduction number (<). If < < 1 then disease-free equilibrium point asymptotically stable globally and HPV will go away. If < > 1 then the endemic equilibrium point and the global asymptotically stable equilibrium point unstable infection-free locally. Then proceed with numeric simulation using MATLAB and its interpretations.